Structured Approach of Designing Data Structure and Algorithms Laboratory Experiments - Husain, Moula; Patil, Somashekhar; Indira, B.; Meena, S. M.; Narayan, D. G. (Journal of Engineering Education Transformations, 2015)
Data structures and algorithms play amajor role in optimizing any non trivial software application. Learning and applying concepts of this course demands a great amount of analytical and logical thinking skills. Teaching this subject at early stages of Information Technology related engineering courses poses a great challenge to the Course Instructors. In this paper, we presented the experience of using structured approach of designing and assessing Data Structures and Algorithms Laboratory experiments. All our laboratory experiments and assignments are well designed and structured to achieve the desired ABET a-k learning outcome elements set for the course. Our experimental case study examples, structured enquiry based experiments and student’s feedback results prove the effectiveness of designing and adopting structured experiments in the laboratory course.